2011
DOI: 10.1002/humu.21656
|View full text |Cite
|
Sign up to set email alerts
|

Protein-protein interaction sites are hot spots for disease-associated nonsynonymous SNPs

Abstract: Many nonsynonymous single nucleotide polymorphisms (nsSNPs) are disease causing due to effects at protein-protein interfaces. We have integrated a database of the three-dimensional (3D) structures of human protein/protein complexes and the humsavar database of nsSNPs. We analyzed the location of nsSNPS in terms of their location in the protein core, at protein-protein interfaces, and on the surface when not at an interface. Disease-causing nsSNPs that do not occur in the protein core are preferentially located… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
145
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(163 citation statements)
references
References 47 publications
17
145
1
Order By: Relevance
“…For example, in a structural survey of nsSNPs, Wang et al (2012) [8] showed that those associated with disease tend to localize to protein interaction interfaces, when found at the protein surface. This finding, which was corroborated by a similar study from the same year [9], builds upon the earlier finding [10] that disease-nsSNPs tend to cluster together, when present at the surface of proteins. In support of a differential distribution of disease and non-disease causing polymorphisms, Wang et al (2012) [8] found that nondisease nsSNPs showed no greater tendency than average to localize to interfaces in the largest human structural interaction network developed to date (4222 interfaces between 2816 proteins).…”
Section: Introductionsupporting
confidence: 86%
“…For example, in a structural survey of nsSNPs, Wang et al (2012) [8] showed that those associated with disease tend to localize to protein interaction interfaces, when found at the protein surface. This finding, which was corroborated by a similar study from the same year [9], builds upon the earlier finding [10] that disease-nsSNPs tend to cluster together, when present at the surface of proteins. In support of a differential distribution of disease and non-disease causing polymorphisms, Wang et al (2012) [8] found that nondisease nsSNPs showed no greater tendency than average to localize to interfaces in the largest human structural interaction network developed to date (4222 interfaces between 2816 proteins).…”
Section: Introductionsupporting
confidence: 86%
“…Many disease-related mutations have been found at the interface of protein complexes [32], [33]. These mutations can disrupt protein-protein interactions, affecting signalling pathways and leading to diseases.…”
Section: Resultsmentioning
confidence: 99%
“…In globular domains, the effect of each mutation is determined by its structural context; whereas mutations in the core may alter the stability of the domain fold, mutations at the surface regions that are involved in molecular recognition may directly affect binding affinities. In fact, many, if not most, disease-related mutations are located at the interface of protein complexes [32], [33]. A small subset of interface residues, called hot spots, are critical for complex formation and their identification is of major importance.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of interfaces for protein functions and biological processes was further confirmed in recent studies by looking at the occurrences of disease-associated mutations [26,106], where the interface regions were found to be enriched in disease-causing mutations. This implies that a residue change at these region is more likely to disrupt protein functions and lead to diseases.…”
Section: Protein Interaction Interfacesmentioning
confidence: 53%